2007
DOI: 10.1007/s00445-007-0146-1
|View full text |Cite
|
Sign up to set email alerts
|

Can crystallization of olivine tholeiite give rise to potassic rhyolites?—an experimental investigation

Abstract: Experiments were conducted to determine whether the rhyolites and basalts of the intraplate silicasaturated potassic suites could be genetically related through crystallization. Extreme crystallization (96-97%) of a high-MgO (10.62 wt%) olivine tholeiite from the Snake River Plain with an initial bulk water content of 0.4 wt% at a mid-crustal pressure of 4.3 kbar generated potassic rhyolitic liquids similar in major element chemistry to those found in the Quaternary rhyolite domes of the Snake River Plain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 42 publications
7
57
0
Order By: Relevance
“…Variation diagrams of trace elements (Zr/Y-Nb/Y), and MgO variations demonstrate a lack of congruity, and elevated concentrations of REE and other incompatible elements suggest either a different magma source or a unique magmatic differentiation scenario. These lavas were generated in a similar fashion as Craters of the Moon lavas, via extreme fractional crystallization accompanied by assimilation (e.g., Whitaker et al, 2006Whitaker et al, , 2008Putirka et al, 2009). However, the decrease in K 2 O/P 2 O 5 ratios (Figure 8) implies that older felsic crust was not involved forming in these flows (or Craters of the Moon), and that extreme fractional crystallization perhaps accompanied by assimilation of slightly older mafic sills was the dominant process.…”
Section: Origin Of Highly Evolved Flow Groupsmentioning
confidence: 99%
“…Variation diagrams of trace elements (Zr/Y-Nb/Y), and MgO variations demonstrate a lack of congruity, and elevated concentrations of REE and other incompatible elements suggest either a different magma source or a unique magmatic differentiation scenario. These lavas were generated in a similar fashion as Craters of the Moon lavas, via extreme fractional crystallization accompanied by assimilation (e.g., Whitaker et al, 2006Whitaker et al, , 2008Putirka et al, 2009). However, the decrease in K 2 O/P 2 O 5 ratios (Figure 8) implies that older felsic crust was not involved forming in these flows (or Craters of the Moon), and that extreme fractional crystallization perhaps accompanied by assimilation of slightly older mafic sills was the dominant process.…”
Section: Origin Of Highly Evolved Flow Groupsmentioning
confidence: 99%
“…Thus, felsic magmas that formed parts of the intrusive complexes in the study area, particularly the Garabal Hill-Glen Fyne complex, 7 could potentially represent the products of high-degree fractionation of the mantle-derived mafic magmas (e.g. Sisson et al, 2005;Whitaker, 2008), or they could represent crustal melts, with or without mixtures of mantle components. Below, we review the evidence for the types of basement materials that might be present in the deep crust of the region.…”
Section: Previous Isotope Researchmentioning
confidence: 99%
“…liquid. Whitaker et al (2008) experimentally explored a similar proposition (crystallisation of hydrous olivine tholeiite) but found that extreme fractionation would be required (96 to rocks and these most felsic rocks. This makes such an origin less likely.…”
Section: Fractionation Modelsmentioning
confidence: 99%
“…For example, anhydrous tholeiitic basalts from mid-ocean ridges and intra-continental volcanism are dominated by olivine, clinopyroxene, and plagioclase crystallization at relatively high magmatic temperatures (1330-900ºC) (Walker et al, 1979;Stolper, 1980;Grove et al, 1992;Villiger et al, 2004;Whitaker et al, 2008 O ratios in a crystallizing tholeiitic melt would be expected due to the high temperatures of crystallization and a crystallizing assemblage rich in plagioclase. In contrast, hydrous basalts typical of subduction zones are characterized by crystallization of anorthite-rich plagioclase, hornblende, pyroxenes, oxides, and garnet at relatively lower temperatures (1200-650ºC) (Alonso-Perez et al, 2009;Jagoutz, 2010;Melekhova et al, 2015;Müntener et al, 2001;Nandedkar et al, 2014;Sisson and Grove, 1993;Sisson et al, 2005 Although Bindeman et al (2004) explored the variations in trajectories expected for melts with different compositions and crystallization conditions his models were based on MELTS modeling results, which does a poor job predicting crystallizing mineralogy and melt compositions for hydrous melts at intermediate compositions.…”
mentioning
confidence: 99%
“…To place better constraints on this problem, we modeled in detail the oxygen isotope trajectories of six liquid lines of descent (LLDs) mostly characterized by near primitive parental melt compositions, crystallization over a wide array of melt compositions (from basalt to high-silica melt), and distinct crystallizing phase assemblages, temperatures, and melt compositions (Table 1). Three of these LLDs are experimentally constrained (Nandedkhar et al, 2014;Villiger et al, 2004;Whitaker et al, 2008) and were selected as they covered nearly the full crystallization interval for their chosen starting compositions (F ranging from 1 to 0.02) and provide detailed constraints on melt compositions, temperatures, and crystallizing minerals. The experimental LLDs range from anhydrous, tholeiitic melts characterized by two pyroxene and plagioclase crystallizing assemblages (Villiger et al, 2004;Whitaker et al, 2008) to hydrous, calc-alkaline melts which crystallized copious amounts of Fe-Ti oxides and amphibole (Nandedkhar et al, 2014 Vantongeren et al, 2011), and the Dariv Igneous Complex, Mongolia (a hydrous, high-K basalt; Bucholz et al, 2014a,b).…”
mentioning
confidence: 99%